Letter - Haldane, Charlotte Franken, 1894-1969
034-0165-001 INTERNATIONAL BRIGADE Dependants and Wounded Aid Committee Patrons: Harry Adams The Duchess of Atholl, MP. H.N. Brailsford Seymour Cocks, MP Ebby Edwards Prof. J.B.S. Haldane. F.R.S. Oliver Harris Will Lawther Sir Walter Layton Earl of Listowel Sir Peter Chalmers Mitchell, C.B.E.. F.R.S., F.Z.S.. D.Sc LL.D. J.B. Priestley Eleanor Rathbone, M.P. Ald. J. Reeves E. Shinwell, M.P. W.J.R. Squance G.R. Strauss, M.P. Wilfrid Roberts, M.P. Ellen Wilkinson. M.P. Hon Secretary: CHARLOTTE HALDANE Telephone: Temple Bar 0178 1 LITCHFIELD STREET, LONDON, W.C.2. March 30th, 1938. The Secretary, General Council Trade Union Congress, Transport House, Smith Sq., S.W.1. Dear Sir Walter, Many of the wounded men and the relatives of British volunteers killed in Spain with the International Brigade are seriously alarmed at the present position in Spain. They are anxious to express their views to you and for this purpose propose to come to Transport House tomorrow, March 31st at 3pm. They make a request to meet you at that time and hear their suggestions as to what could be done to help the democratic forces in Spain. We hope it will be convenient for you to see them. Yours sincerely Charlotte Haldane (Hon. Secretary). 292/946/34/165